IMPLEMENTASI TONGUE TWISTERS DALAM PEMBELAJARAN PRONUNCIATION DI SMK NEGERI 1 BANDUNG - Triani, Caterina Nova; Huda, Moh. Choirul (Yayasan Amanah Nur Aman, 2025)
Tongue twister is one method of learning pronunciation that students find interesting and fun. Tongue twisters are phrases that are hard to say quickly, usually because they sound similar yet different. This research aims to find out how the implementation of tongue twister in learning pronunciation at SMKN 1 Bandung, especially in the extracurricular English Club. researchers in this case used a qualitative descriptive analysis method. three research tools, namely observation and teacher interviews and student questionnaire sheets, were used to collect data. 1 teacher as well as 8 student of the English Club of SMKN 1 Bandung in the academic year 2024/2025 were used as research participants. Findings show that using tongue twisters-combined with repetition, gradual speed increase, and rhythmic patterns-helps students articulate words more clearly, gain confidence, and enjoy the learning process. The teacher's integration of music and student creativity also played a role in enhancing engagement.